2019
DOI: 10.7759/cureus.5908
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Use for Improving Functional Ischemic Stroke Outcomes

Abstract: ObjectiveTo assess the effect of antidepressants on functional post-stroke recovery, we conducted a retrospective analysis among acute ischemic stroke patients with a subgroup analysis of severe stroke cases, assessing outcomes through 18 months.MethodsA retrospectively gathered ischemic stroke population was obtained from an institutional database. Grouping was via intention-to-treat with antidepressant use post-stroke or lack thereof. Patients with severe stroke (NIHSS ≥ 21) were further analyzed independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…An important marker of the quality of patient care, satisfaction increasingly gained more importance in quantifying the result of stroke that the satisfaction with the care of the stroke patients' increases might relieve both the patients and caregivers' stress as well as increasing quality of life. In the study of Heiberger et al was reported in their study in which they have assessed the satisfaction of patients and their caregivers that those who experience the impact of stroke less are more satisfied with life (Heiberger et al, 2020). In addition, it was found that the care workers with high perception of care load have low levels of life satisfaction).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important marker of the quality of patient care, satisfaction increasingly gained more importance in quantifying the result of stroke that the satisfaction with the care of the stroke patients' increases might relieve both the patients and caregivers' stress as well as increasing quality of life. In the study of Heiberger et al was reported in their study in which they have assessed the satisfaction of patients and their caregivers that those who experience the impact of stroke less are more satisfied with life (Heiberger et al, 2020). In addition, it was found that the care workers with high perception of care load have low levels of life satisfaction).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported 158 old stroke patients and their caregivers that after a planned discharge training, the levels of being more prepared to care and the levels of their satisfaction of their needs being met are considerably higher (Shyu, Chen, and Chen, 2008). In addition, in some studies it was determined that the stroke training and emotional support given to patients and their caregivers increase satisfaction (Heiberger et al, 2020;LeLaurin et al, 2020). It was demonstrated in several studies on the caregivers of stroke patients that initiatives intended for caregivers have improved the perception of being prepared for care, and enhance particularly their confidence, self-sufficiency, competence, and their perception of the quality of care (Hall, Crocker and Clarke, 2019;Crocker, Brown and Lam, 2021).…”
Section: Introductionmentioning
confidence: 99%